2014
DOI: 10.1002/jsfa.6525
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilisation increases biogenic amines and amino acid concentrations inVitis viniferavar.Rieslingmusts and wines

Abstract: Nitrogen fertilisation has a significant effect on amines formation in musts and wines. Furthermore, during fermentation, ethylamine and histamine increased while other amines were presumably serving as N sources during fermentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…In agreement with our results, some authors 6,7,34,37 have suggested that total nitrogen content present in grapevine leaf tissues, must and wine are parameters characterized by the nitrogen grapevine status. The major amount of nitrogen in grapes is present in the form of proteins, amino acids and ammonium, 1 37 with cv.…”
Section: Relationship Between Leaf Nitrogen Content and Biogenic Aminessupporting
confidence: 94%
See 2 more Smart Citations
“…In agreement with our results, some authors 6,7,34,37 have suggested that total nitrogen content present in grapevine leaf tissues, must and wine are parameters characterized by the nitrogen grapevine status. The major amount of nitrogen in grapes is present in the form of proteins, amino acids and ammonium, 1 37 with cv.…”
Section: Relationship Between Leaf Nitrogen Content and Biogenic Aminessupporting
confidence: 94%
“…Wine oenological parameters from the three experimental treatments (CT, conventional tillage; B, blade cover crop; CL, clover cover crop), in 2009, 2010, 2011 and 2012 seasons Biogenic amine concentration (mg L −1 ) from the three experimental treatments (CT, conventional tillage; B, blade cover crop; CL, clover cover crop), in 2009, 2010, 2011 and 2012 seasons For each biogenic amine and year, different letters indicate significant differences among treatments (P ≤ 0.05). n.d., not detected.and a high proportion of the biogenic amines are synthesized during malolactic fermentation 34. Although we have not found any studies reporting the influence of cover crops on wine biogenic amine concentration, Fourie et al3,4 with cv.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Amino acids play important roles in plant growth and secondary metabolite production (Calvo et al, 2014). The application of amino acids to grapevine is generally accomplished through the use of fertilizers to increase nitrogen-containing substances in grape berry (Smit et al, 2014). Foliar treatment with phenylalanine affected the phenolic content and aroma composition in grapevine (Garde-Cerdán et al, 2014;Portu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve must N composition, different studies have been carried out applying N to the vineyard. However, a high rate of N fertilization can result in the accumulation of negative compounds in wine, such as biogenic amines and ethyl carbamate (Smit et al, 2014). A traditional way to improve wine volatile composition has been the soil N fertilization.…”
Section: Introductionmentioning
confidence: 99%